The Application of Role Playing Method in the Digestive System Material Learning in SMPN 4 Geyer - Susilo, Barep Purbo; Kartijono, Nugroho Edi; Purwantoyo, Eling (Journal of Biology Education, 2020)
This research purposes to know students activity and learning result in the application of Role Playing in the digestive system material. The study used Pre- Experimental One-Shot Case Study design. The population of the study is all students of grade VIII of SMP N 4 Geyer. The sample of the study is VIII B and VIII E and use Simple Random Sampling method to choose the sample. The observation results of the students’ activity from both classes are 91.7% and 88.5% with good and very good category. The learning outcomes on knowledge and skill aspects from both classes are 95.8% and 88.4% students are included in good and very good category. The classical completeness is 95.8% and 92.3%. The teacher and students’ response show positive respond toward the applied learning method.